The correlation between economic diversification and sustainable development of the Russian regions - R. A. Abramov (Вестник университета)
Diversity of economic activities and their diversification determine the key factors of sustainable development of the Russian regions.    The relevance of this study lies in the search of connection between the present economic process and such parameters of sustainable development as social well-being, economic and environmental stability.   The research is based on examination of data of the Federal State Statistics Service, its publications, and other scien tific sources. The methodology includes a comprehensive analysis of economic indicators of diversification and their correlation with the three indices described above. The presented results demonstrate a direct connection between the level of economic diversification in the regions and their sustainable development. It is shown that regions with a more varied economic structure have higher indicators in the field of social stability, economic growth, and environmental safety. The authors determine that diversification as a whole does not depend on the production orientation or the traditional industrial equipment of a region. It is identified that innovative practices may be implemented in almost all subjects in case if a number of administrative barriers will be overcome. It is revealed that the level of sustainability of regional development directly depends on the degree of diversification of economic processes.